Partitions of the set of nonnegative integers with the same representation functions - Kiss, Sándor Z.; Sándor, Csaba (Discrete mathematics, 2017)
For a set of nonnegative integers S let RS(n) denote the number of unordered representations of the integer n as the sum of two different terms from S. In this paper we focus on partitions of the natural numbers into two sets affording identical representation functions. We solve a recent problem of Chen and Lev.